SAILING APPROVAL LETTER FOR COMMERCIAL SHIP - Agus Majid; Osgar S Matompo; Muliadi Muliadi; Ghazali Abdullah (Fakultas Hukum Universitas Muhammadiyah Palu, 2021)
The method used in writing this thesis is to use a normative juridical research approach. This study aims: (1).To find out the Legal Arrangements Regarding Sailing Approval Letters for Commercial Ships (2) To find out the Legal Implications for Commercial Ships that are Not Seaworthy but Have Sailing Approval Letters. The results of this study are (1). Issuance of Sailing Approval Letter is regulated in Article 219 of Law Number 17 of 2008 concerning Shipping and is followed up by Government Regulation Number 82 of 2014 concerning Procedures for the issuance of Sailing Approval Letter. In this provision, ships carrying out voyages, including commercial ships, are required to have a Sailing Approval Letter issued by the harbormaster with the stipulation that the ship is seaworthy in practice. Most of the commercial ships that occur at sea are caused because the ship is sailing in a state that is not seaworthy and the implications of the ship accident are the porter who is affected, is considered negligent, must also be responsible for his policy of issuing a Sailing Approval Letter (SPB).